ISOLASI OLIGOSAKARIDA MADU LOKAL DAN ANALISIS AKTIVITAS PREBIOTIKNYA - Umul Karimah; Yogi Nur Anggowo; Syamsul Falah; Suryani Suryani (Jurnal Gizi dan Pangan, 2011)
The objective of this study was to isolate oligosaccharides from local honey of Pulau Sumbawa and province of Kalimantan Timur and to analyze its prebiotic activity in vitro. Oligosaccharides were isolated with activated charcoal adsorption and ethanol treatment. Effectiveness of this method was evaluated by Thin Layer Chromatography and colorimetry. The isolates were then being a sample to prebiotic examination. Honey from Sumbawa forest has higher oligosaccharides content than honey from Kalimantan. Qualitative and quantitative assays showed that oligosaccharide isolation method was effective to concentrate the oligosaccharide with high degree of polymerization but ineffective for mono- and disaccharides removal. The highest percentages of hydrolysis of oligosaccharide from Sumbawa and Kalimantan by mimic gastric juice were 1.78% and 0.59 %. Whereas, the hydrolysis was higher with amylase, 11.87% for Sumbawa and 21.03% for Kalimantan honey oligosaccharides. Prebiotic activity was 0.32, and 0.09 for honey oligosaccharide from Sumbawa and Kalimantan respectively. Honey oligosaccharide from Sumbawa presented higher prebiotic activity than inulin as prebiotic reference (0.11). GC-MS chromatogram showed L. acidophilus cultured in media added with Sumbawa honey oligosaccharide produced lactic acid as the highest metabolite (48.01%).